The Effect of A Combination of Marmet Techniques and Post Partum Mothers Breast Care on the Slow Delivery of Breast Milk - Simorangkir, Lusy Mariana; Silaban, Verawaty Fitrinelda; Lisu, Lisu; Litunzira, Litunzira; Sitanggang, Lusiana; Simatupang, Maimunah (Indonesian Journal of Global Health Research, 2024)
Breast milk is the most perfect food for babies, giving breast milk to babies aged 0-6 months can provide high-value nutrients needed for growth and development of the brain and nerves, can make the baby's body immune to several diseases, Providing Water Exclusive breast milk (ASI) for 6 months throughout the world is still not in accordance with the World Health Organization (WHO) breast milk recommendations which state that breastfeeding is an unrivaled way of providing ideal food for healthy growth and development for babies. Objective: in this study is To determine the smooth flow of breast milk before the Marmet Technique and Breast Care for Post Partum Mothers on the Smooth Expression of Breast Milk at the Pratama Mariana Clinic Deli Serdang, Method: This research uses quasi-experiments. The subject group was observed before the intervention and observed again after the intervention, using the One Group Pre-Test and Post-Test research method. The research began in October 2023. This research involved collecting univariate and bivariate data as well as collecting data from 40 respondents . Results: the research that has been carried out has obtained a Z value of -5.477 with a P value = 0.000, where the P value < α (0.05) conclusion: There is a significant influence of providing the Marmet Technique and Post Partum Mother's Breast Care on the Smooth Expression of Breast Milk in Pratama Mariana Clinic Deli Serdang.